The effect of creep damage model formulation on crack path prediction (Fracture and Structural Integrity, 2019)
The stress, strain rate and process zone with respect to the creep-crack growth are analyzed by employing damage-evolution equations. The damage models for the fracture of the process zone are represented using a stress and ductility based formulation. Special attention has been addressed in the present study to the influence of the creep damage model formulation on the on crack path prediction. To evaluate the significance of dominating fracture mechanism a comparison of the cases for pure mode II is considered. It was observed that in the case of stress based model one side of the notch, dominated by tensile stresses, blunts, while the other side, dominated by shear strains, sharpens. In the case of ductility based model, there is a tendency for creep damage to localize only at the blunted part of the notch. This because the highest tensile hydrostatic stress and crack-tip constraint always occur near the blunted part of the notch. In this region, the crack growth direction and general creep damage zone deviate from the initial crack plane. As a result of numerical calculations the consequence of the crack deviation angle values, crack length increments and finally crack path were determined.
Keywords: creep damage; limit stresses and strains; crack path